SETTLEMENT OF PAST GROSS VIOLATIONS OF HUMAN RIGHTS BY THE JOKOWI GOVERNMENT - Thamrin, Husni (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
The pendulum of resolving the past gross human rights violations has begun to move a little forward in the second term of President Jokowi's administration. It took 8 years for President Jokowi to start solving the past gross human rights violations. Even though this is a program that he launched when he was elected for the first time in 2014. This research is aimed at exploring the policies of the Jokowi government in resolving the past gross human rights violations from the beginning to the present, including finding at the advantages and disadvantages. The research method used a qualitative, descriptive approach by examining emerging policies and viewing and analyzing a series of regulations related to their relationship with the implementation of policies in the field. From this research obtained the wall of impunity is still role to intervene a process, lack of understanding and half-hearted management to resolve the past gross human rights violations gripped the government's steps. Not to mention the existence of sabotage and stowaways to resolve the gross violations of human rights, whether they were aware of it or not within the palace. The President Jokowi's series of policies in resolving past gross human rights violations by issuing Presidential Decree Number 17 of 2022, Presidential Instruction of the Republic of Indonesia Number 2 of 2023 discusses the Implementation of Recommendations for Settlement of Rights Violations Serious Human Rights and Presidential Decree Number 4 of 2023 passed various existing regulations to resolve the past gross human rights violations.